To eat or not to eat: premature sprouting (vivipary) in cereal and fruit crops - Cota-Sánchez, Jorge Hugo (2023)
Vivipary also known as the precocious germination of seeds while still attached to the mother plant or fruit, it’s a relatively common phenomenon in angiosperms. However, the proliferating seedlings though interesting to look at, deter customers from eating the fruits. Similarly, vivipary is an adverse phenomenon for the agroindustry because of the lowest quality and palatability of fruits as well as lower seed set and viability. This paper highlights the taxonomic occurrence of vivipary in cereal and crop plants and the detrimental effects of this phenomenon in agricultural crops. According to literature sources, there are 38 fruit crops in which vivipary has been reported. The families Cucurbitaceae, Poaceae, Rutaceae, and Solanaceae include the fruits with the highest incidence of vivipary in the markets.